1962: Bronisław Baczko in the Wake of Jean-Jacques Rousseau and Maurice Merleau-Ponty - Gabriella Silvestrini (Scienza & Politica)
The article starts from a very short text on Rousseau that Bronisław Baczko published in 1962 in the «Journal de Genève», Plus on croit le figer, plus il se dérobe, which is offered here as an appendix in Italian translation. Beginning with a detailed commentary on the text, the thesis we intend to demonstrate is that for the Polish historian the encounter with the works of Maurice Merleau-Ponty was crucial not only for the interpretation of Rousseau, but also for the shift from philosophy and the history of philosophy to the history of “imaginaries” and mentalities, as well as for his peculiar way of conceiving the profession of the historian and his responsibility.